Assessment of Water Quality Index of Beratan Lake Using NSF WQI Indicator - Ni Made Hegard Sukmawati (WMJ (Warmadewa Medical Journal), 2019)
Beratan Lake is one of the lake in Bali which serves as place for agriculture, aquaculture, as well as tourism and recreational attractions. The growing number of facilities around the lake potentially increases the number of waste discharge to the lake as most of the industry do not equipped with necessary waste management plant. The aim of this study is to assess the water quality in Beratan Lake and later be used to improve the water management. Method: Five stations for water sampling were purposively chosen as representation of each side of the lake. The coordinate locations were recorded by Epicollect. Nine water quality parameters were measured for each water samples from each station: temperature, pH, total dissolved solids (TDS), dissolved oxygen (DO), biochemical oxygen demand (BOD), phosphate, nitrate, turbidity, and fecal coliform. The water quality were calculated based on National Sanitation Foundation Water Quality Index (NSFWQI). Result: NSFWQI for water of Beratan Lake was 78 which indicates good quality. Although this result has been satisfying, fecal coliform and pH showed score lower than 55, thus, the two parameters need to be modified to improve water quality for further use.